ANALISIS ISI SENSASIONALISME BERITA KRIMINAL (STUDI KASUS PROGRAM INEWS DAN KOMPAS SULSEL) - Mitha Mayestika Kuen; Yuweni Puji Saputri (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Indonesia Timur, 2019)
ABSTRACTThis study discusses the Analysis of the Content of Sensationalism in Criminal News (Case Study of the Inews Program of South Sulawesi and KompasSulsel). The basis of this research began because of the fierce competition between television, newspapers and radio and the limitations of the medium, making television shift from the emphasis on public conversation leading to entertainment. There was a tight competition in the Market News. This condition provides an increase in a phenomenon called